Special Speed Exercises For Developing Motor Response Time And Its Effect On Defense Player Motor Skill In Basketball 3×3 Under Eighteen - Hanoon, Wassan (Journal of Physical Education, 2016)
The problem of the research lies in the modern sport of 3×3 basketball and finding new means for developing this sport physically. No previous researches tackled physical abilities specially response speed. The researcher aimed at designing speed exercises for 3×3 basketball defense players U18 and identifying their effect on response speed development.The researchers used the experimental method. The subjects were (6) Air force 3×3 basketball players. The training program consisted of three training sessions per week for 8 weeks. The data was collected and treated using SPSS to come up with the results. The researchers concluded that the special physical exercises develop the speed of motor response of 3×3 basketball defense players.